(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Fluvoxamine, an antidepressant belonging to serotonin reuptake inhibitor class exhibits maximum absorption through oral route of administration. The objective of current research is to formulate mouth dissolving fluvoxamine films by employing super disintegrants. The Central Composite Design (CCD), employed to examine the effects of amount of HPMC E15 (A), amount of eudragit RL 100 (B), amount of polyethylene glycol (PEG 4000) (C) on response variables tensile strength, disintegration time and cumulative % drug released. 27 formulations prepared according to CCD and evaluated for physico chemical parameters and in vitro dissolution studies. Fluvoxamine mouth dissolving films formulated by employing solvent-casting method using HPMC E15, eudragit RL100 and PEG 4000. CCD employed to optimize the effective dosage of formulation superdisintegrants. The formulation FF15 with maximum tensile strength of 55.63±1.37 mg, least disintegration time of 10±1.85sec and highest drug release of 98.29±1.87 % is chosen optimal formulation with maximum content uniformity and folding endurance. From in vivo bioavailability studies Cmax and Tmax of the fluvoxamine optimized mouth dissolving film formulation was significant (p<0.05) as compared to the fluvoxamine marketed product formulation. AUC0-∞ infinity for optimised formulation was higher (733.84±2.04 ng.h/ml) than the fluvoxamine marketed product formulation 485.67±1.54 ng.h/ml. Statistically, AUC0-t of the optimized mouth dissolving film formulation was significantly higher (p<0.05) as compared to fluvoxamine marketed product formulation. In vivo pharmacokinetic studies in rabbits confirmed the quick release and increase in bioavailability for Fluvoxamine from optimized mouth dissolving film formulation as compared to the fluvoxamine marketed product formulation.